2006
DOI: 10.1111/j.1471-4159.2005.03597.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and extrinsic erythropoietin enhances neuroprotection against ischemia and reperfusion injury in vitro

Abstract: This study was designed to investigate the neuroprotective effect of intrinsic and extrinsic erythropoietin (EPO) against hypoxia/ischemia, and determine the optimal time-window with respect to the EPO-induced neuroprotection. Experiments were conducted using primary mixed neuronal/astrocytic cultures and neuron-rich cultures. Hypoxia (2%) induces hypoxia-inducible factor-1a (HIF-1a) activity followed by strong EPO expression in mixed cultures and weak expression in neuron-rich cultures as documented by both w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 25 publications
2
58
0
1
Order By: Relevance
“…Pretreatment with Epo prevents neuronal death in in vitro models of hypoxia and reduces ischemic damage in various animal models of stroke (Jin et al, 2000;Liu et al, 2006). The correlation of reduced expression of both Epo and Glut-1 with increased cell death emphasizes the importance of Cdk5 activity in hypoxic adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment with Epo prevents neuronal death in in vitro models of hypoxia and reduces ischemic damage in various animal models of stroke (Jin et al, 2000;Liu et al, 2006). The correlation of reduced expression of both Epo and Glut-1 with increased cell death emphasizes the importance of Cdk5 activity in hypoxic adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Transduction profiles of the AAV9 vectors after striatal injections were similar to previous findings using AAV2 or AAV5 vectors. 32 It has been suggested that EPO exerts its neuroprotective effects on CNS neurons through multiple mechanisms, including anti-apoptosis, 5,33 anti-inflammation, 34 inhibition of glutamate release, inhibition of reactive oxygen species formation, 35 activation of Akt/ protein kinase B through the phosphoinositide 3-kinase pathway, 5 and activation of Janus kinase-2 and nuclear factor-kB signaling pathways. 36 We have recently showed that intrastriatal administration of EPO protects nigral DA neurons from cell death induced by 6-OHDA in part through an anti-inflammatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…was shown to protect BBB breakdown after experimental seizure (Uzum et al, 2006) and to reduce infarct size after ischemia/reperfusion (Liu et al, 2006). An in vitro study has also shown that EPO protects against the VEGF-induced permeability of the BBB, decreases the levels of endothelial nitric oxide synthase, and restores junction proteins (MartinezEstrada et al, 2003).…”
Section: Discussionmentioning
confidence: 99%